(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nashik district is famous in whole Maharashtra for grape cultivation In this present paper an attempt has been made to analyze the General land use and fruits crops pattern in Nashik District Special reference grapes and banana. The study is based on secondary source of data obtained from the district statistical handbook. Agricultural land use pattern is always influenced by physical, weathersocio-economic and technological factors. In this paper a study has been done to find out the General land land-use pattern and grapes and banana fruit crop present scenario in Nashik District for the year 2011-12 to 2022-23 Based on the information in the research essay, the total mango area in Nashik district is 4079 in the year 2011-12. 28 hectares i.e. 5.4 percent and in the year 2022-23 the mango fruit crop area increased to 60.8 percent. Similarly, when the grape crop was studied in the year 2011-12, the total grape area in Nashik district was 55750 hectares (73.8) while the grape crop decreased to 34.2 percent in the year 2022-23.